2002
DOI: 10.1002/ett.4460130507
|View full text |Cite
|
Sign up to set email alerts
|

Spreading sequences for uplink and downlink MC‐CDMA systems: PAPR and MAI minimization

Abstract: Abstract. This paper deals with spreading sequences selection for downlink and uplink Multi-Carrier Code Division Multiple Access (MC-CDMA) systems with the aim of minimizing the dynamic nnge of the tcansrnitted rnulticamer signal envelope and the multiple access interference. The crest factor of orthogonal and non-orthogonal sequences are compared analytically and by simulation for downlink and uplink phase shift keying MC-CDMA transmissions. Then, in order to minimize the multiple access interference produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 11 publications
2
33
0
Order By: Relevance
“…The numerical results we obtained confirmed that the new family of even BCH-derived sequences contains a high number of (quasi-orthogonal) sequences with low correlation levels, better than those presented by the even sequences of the recent UMTS system [16,17] and higher PGs, even when compared with the LS sequences [19,25] of the LAS-CDMA system. These characteristics can make the even BCH-derived sequences very attractive in fading dispersive channels, either in synchronous or quasi-synchronous channels.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The numerical results we obtained confirmed that the new family of even BCH-derived sequences contains a high number of (quasi-orthogonal) sequences with low correlation levels, better than those presented by the even sequences of the recent UMTS system [16,17] and higher PGs, even when compared with the LS sequences [19,25] of the LAS-CDMA system. These characteristics can make the even BCH-derived sequences very attractive in fading dispersive channels, either in synchronous or quasi-synchronous channels.…”
Section: Introductionsupporting
confidence: 62%
“…For instance, the well-known orthogonal binary Walsh-Hadamard sequences are used to eliminate the MAI in synchronous channels (in-phase channels), like the downlink transmission in mobile communication systems. However, these sequences have the worst values of cross-correlation when compared with other (orthogonal and non-orthogonal) PN sequences usually used in asynchronous (or quasi-synchronous) CDMA systems [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In the downlink system, the spread data of all active users are added synchronously and mapped on to the L c sub-carriers [7]. The sequence, B (k) i is applied to a serial-to-parallel converter and multiplied by the k with the user specific spreading code of Walsh C (k) i of length L [5], [7], In [31], [7] confirmed that the WalshHadamard codes are the best choice for the downlink, also for the minimization of multiple access interference.…”
Section: Model Mc-cdma Systemmentioning
confidence: 99%
“…Nobilet et al, Garía-Armada et al, and Saito el al. evaluated the PAPR properties of MC-CDMA both uplink and downlink for various channelization codes [7]- [9]. On the other hand, we have analyzed the effect of a scramble code on the PAPR performance, and concluded that a scramble code eliminates the differences amongst the PAPR properties of channelization codes [10].…”
Section: Introductionmentioning
confidence: 99%